Persepsi Guru tentang Literasi Sejarah di Era Disinformasi: Implikasinya terhadap Pembelajaran Sejarah - Roro Wilis; Wilis, Roro; Jovanda, Reynaldy; Parhamah, Winda Pitriani; Imroah Laina Retno Mukti Kusuma; Hidayat, Syahrul (Paedagogie, 2026)
This study aims to analyze teachers' perceptions of historical literacy in the era of disinformation and their implications for the implementation of history learning. A qualitative approach with a multiple case study design was used to understand patterns and explore data in depth on the research subjects, namely history teachers and student representatives at SMA Negeri 6 Yogyakarta and SMA Negeri 9 Yogyakarta. Data collection was carried out through direct observation, in-depth interviews, and document analysis; while secondary sources were obtained from an inventory of indexed scientific articles relevant to the research topic. Data analysis was carried out using triangulation of sources and techniques. The results of the study indicate that a proper understanding of the concept of historical literacy can contribute to preparing students to be adaptive in the era of disinformation. History teachers at SMA Negeri 6 Yogyakarta and SMA Negeri 9 Yogyakarta define historical literacy not only as the ability to read and write, but also as the ability to analyze historical sources, verify and compare various pieces of information, and construct interpretations based on historical evidence. These perceptions have implications for the implementation of student-centered learning, the selection of contextual and controversial materials, and the use of authentic assessments oriented towards Higher Order Thinking Skills (HOTS).